Functional Involvement of Melatonin and Its Receptors in Reproductive Regulation of the Marine Teleost, Large Yellow Croaker (Larimichthys crocea) - Xudong Liang; Jixiu Wang; Baoyi Huang; Haojie Yuan; Yucheng Ren; Chenqian Wu; Tianming Wang; Jingwen Yang (Fishes)
Melatonin is a critical regulator of biological rhythms across organisms, transducing light signals into neuroendocrine signals that facilitate reproductive regulation in response to environmental cues. However, the precise mechanisms through which melatonin regulates reproduction in fish require further investigation. In this study, we employed molecular and organizational biological techniques to examine the expression patterns of melatonin and its five receptor subtypes (LcMTNR1A1, LcMTNR1A2, LcMTNR1B1, LcMTNR1B2, and LcMTNR1C) in various tissues of the large yellow croaker (Larimichthys crocea). Our results revealed significant expression of all receptors in the pituitary and testes, with distinct gender differences, including a lack of expression in the ovary. Moreover, our data indicate that melatonin and its receptors are primarily expressed during stage III, highlighting their role in sexual maturity. Enzyme- linked immunosorbent assay (ELISA) results further demonstrated that in vitro melatonin incubation in the brain of L. crocea influenced gonadotropin-releasing hormone (GnRH) and testosterone secretion in a dose-dependent manner, suggesting actions beyond the classical hypothalamic–pituitary–gonadal (HPG) axis. Overall, our findings provide new evidence supporting the role of the melatonin system in reproductive regulation in marine teleosts.